Redox and coordination chemistry of diguanidino-benzene ligands with crown ether functions as secondary coordination spheres - Haaf, Sebastian; Henel, Carmen L. M.; Kreis, Franka; Bruttel, Melanie; Kaifer, Elisabeth; Osterbrink, Johanna; Hübner, Olaf; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2024)
In this work, we report the synthesis and characterization of new redox-active tetraguanidine ligands with crown ether functions as secondary coordination spheres, namely a 2,3,12,13-tetraguanidino-dibenzo-18-crown-6 and two 2,3,16,17-tetraguanidino-dibenzo-24-crown-8 derivatives. Metal ion and organic cation coordination to the secondary crown ether coordination sphere is studied and its effect on the electronic structures and redox properties analysed. Then, the coordination and redox chemistry of di- and tetraguanidine ligands with crown-ether functions is evaluated. Copper and cobalt complexes with the metals bound to the guanidino functions are prepared. Especially, the redox chemistry of CoII cobalt complexes with and without metal ion encapsulation to the crown ether function is compared. The results contribute to the development of a supramolecular chemistry with redox-active guanidine ligands.